Subcritical Water Hydrolysis of Comb Pen Shell (Atrina pectinata) Edible Parts to Produce High-Value Amino Acid Products - Byung-Soo Chun; Seung-Chan Lee; Truc-Cong Ho; Jean-Bosco Micomyiza; Jin-Seok Park; David Nkurunziza; Hee-Jeong Lee (Marine Drugs, 2022)
Artina pectinata (Comb pen shell, CPS) is a high-protein source that contains a variety of essential amino acids. Subcritical water hydrolysis (SWH) was used to recover amino acids from the posterior adductor muscle (PAM), anterior adductor muscle (ADM), and mantle. The temperatures ranged from 120 °C to 200 °C, and the pressure and time of hydrolysis were 3 MPa and 30 min, respectively. Further characterization of the hydrolysates was performed to ascertain amino acid profiles and biofunctional properties. The hydrolysates contained more free amino acids than the untreated samples. Antioxidant activity of treated samples increased as SW temperatures increased. At 200 °C, those inhibiting ACE had a maximum antihypertensive activity of 200 °C in 1% PAM, ADM, and mantle with 85.85 ± 0.67, 84.55 ± 0.18, and 82.15 ± 0.85%, respectively, compared to 97.57 ± 0.67% in 1% standard captopril. Perhaps the most significant finding was the predominance of taurine in the three parts following SW treatment at 120 °C. The hydrolysates may be of considerable interest for use in food or energy drinks. SWH demonstrates efficacy in recovering amino acids, particularly taurine, from edible parts of A. pectinata.